The K3 Policy Strategy To Improve Worker Safety In PT. Nusa Raya Cipta TBK Medan In 2023 - Eva Kristina Pelawi; Ermi Girsang; Ali Napiah Nasution (Sean Institute, 2024)
Labor has an important role and position as actors and development goals. To improve the quality of the workforce, employment development is needed aimed at increasing protection for workers. Occupational safety and health (K3) has a very important role in every organization. Data shows that there are still many companies that have not implemented an effective K3 policy strategy, as evidenced by the high numbe r of work accidents and fatalities in Indonesia. This research combines several methods, namely interviews and library or literature studies. Data collection uses in - depth interview techniques, observation and documentation. The validity and reliability of the data was carried out by source triangulation. The data analysis used in this research uses inductive qualitative data analysis techniques. Activities in data analysis include reduction, data presentation and drawing conclusions. The research results show that K3 policy strategy planning is implemented in accordance with government regulations contained in PP No. 20 of 2012. Supervision is carried out with company references in the form of Law no. 1 of 1970 and ISO 45001:2015 where the number of K3 supervision is 2 Safety Officers or according to the needs of the project. Meanwhile, reporting is carried out internally, containing incident reports to the Project Manager and Branch Manager which are carried out via telephone or verbally by the safety officer on duty